First WHO Model List of Essential in Vitro Diagnostics (Technical report series (World Health Organization), 2019)
In May 2018 the World Health Organization (WHO) published the first ever Model List of Essential In Vitro Diagnostics (EDL). The objective of the list is to help countries develop or update their national essential diagnostics lists raise awareness and political will guide procurement and regulation policies and improve access to the most important in vitro diagnostics that all countries need to make available to their populations particularly in low-resourced countries. It will also contribute towards health systems strengthening and realizing universal health coverage. The 1st EDL list includes 62 test categories divided into two levels and two categories: - Level I: primary care settings where no or minimal laboratory services are available - Level II: facilities with laboratories - Category a: general IVDs - Category b: disease-specific IVDs